Dual-Polarized Antenna Based on Metal Ring and Microstrip Patch - Lizhong Song; Sai Li, (Applied Computational Electromagnetics Society Journal (ACES), 2021)
Based on the principle of the complementary antenna, a kind of dual-polarized antenna element is studied, which combines the metal ring and rectangular microstrip patch. The antenna separates the rectangular microstrip patch and the metal ring on a vertical space, and the metal ring is equivalent to a current radiation source. The rectangular microstrip patch is equivalent to a magnetic flux radiation source, which respectively radiates and receives two orthogonal polarized electromagnetic wave components to achieve dual polarization. A metal reflector ground is introduced to realize the uni-direction radiation pattern, and the front-to-back ratio of the pattern has been improved. The simulation results show that the isolation between two polarization ports is 22dB within the frequency range of 4.94GHz~5.06GHz. The measured results of the fabricated antenna indicate that the Voltage Standing Wave Ratio (VSWR), port isolation degree and the cross polarization level can satisfy technical requirements. And design effectiveness of the dual-polarized antenna in this paper was proved. The dual-polarized antenna studied in this paper has been suitable for some application fields such as phased array radar and the research results lay the technical foundation for the practical engineering application.